The Advocacy Strategy of The Refugee Council of Australia (RCOA) for Temporary Rights to Work for Refugees under The Australia’s ‘Balancing Act' - Fachrurreza, Ahmad Mujaddid; Nihayati, Arina; Larasati (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The Refugee Council of Australia (RCOA) is the important actor in advocating for temporary work rightsfor refugees amid the complexity of Australian asylum policy. This study analyses RCOA’s advocacystrategies in responding to asylum policy restrictions, particularly through the constructivist approachthat emphasises the importance of discourse and social norms. Using the qualitative methods throughthe document analysis of policy papers, public campaigns, and submissions to the government, this study adopts the advocacy strategy framework to examine how the RCOA operates in a policy environment shaped by the “balancing act” between the border security and humanitarian obligations. The research findings show that RCOA utilises the evidence-based lobbying, coalition building, and public engagementto drive policy change and reframe the narration around the refugees. Despite facing structural andpolitical barriers, RCOA’s advocacy contributes to increased public awareness and opens up space formore inclusive policy discussions. This study highlights the important role of civil society in advocating for refugee rights through approaches based on the dignity, social inclusion, and economic contribution.